2016
DOI: 10.1016/j.jand.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Nine Family Dinner Frequency Measures and Child Weight, Dietary, and Psychosocial Outcomes

Abstract: Background Family meal frequency has been consistently and significantly associated with positive youth dietary and psychosocial outcomes but less consistently associated with weight outcomes. Family meal frequency measurement has varied widely and it is unclear how this variation may impact relationships with youth weight, dietary, and psychosocial outcomes. Objective This study assesses how five parent/caregiver-reported and four child-reported family dinner frequency measures correlate with each other and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 38 publications
1
42
1
Order By: Relevance
“…children with cystic fibrosis or diabetes) and (iii) the study reported insufficient statistics to calculate an effect size. Using these criteria, we arrived at a total of 57 studies .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…children with cystic fibrosis or diabetes) and (iii) the study reported insufficient statistics to calculate an effect size. Using these criteria, we arrived at a total of 57 studies .…”
Section: Methodsmentioning
confidence: 99%
“…who was present at the table) and found small differences in weight outcomes. More specifically, measures asking about ‘sitting and eating together’ revealed stronger effects than measures that addressed either sitting together or eating together .…”
Section: Introductionmentioning
confidence: 95%
“…Fulkerson et al (2009) reported that adolescents who did not eat dinner with their families in the week before the study were almost 3 times more likely to be overweight [23]. Horning et al (2016), evaluating different measures of FFM, as reported by parents and adolescents, and the relationship between these variables and BMI z-scores, found, in adjusted analyses, that measures of sitting and eating together were inversely related to BMI z-scores in adolescents [27] In another study, Horning et al (2017) evaluated the moderating role of FFM in the relationship between meal context and NS of parents and adolescents, and the results suggested that FFM amplifies the relationship between healthy eating behavior and BMI in the context of family meals [28]. showed that infrequent family meals were consistently associated with higher BMI z-scores in both boys and girls [31].…”
Section: Main Outcomes Of Ffm and Nsmentioning
confidence: 99%
“…Horning et al (2016) identified a significant association of the frequency of family dinners with dietary quality and fruit and vegetable intake, as assessed by the Healthy Eating Index (HEI) [27]. Dietary quality and the intake of fruits and vegetables at dinner were also assessed by Arcan et al (2019), who found that individuals with higher FFM were more likely to fill half their plate with fruits and vegetables, although they did not differ from their peers in terms of dietary quality [41].…”
Section: Plos Onementioning
confidence: 99%
“…First, this study analyzed the direct relationships between maternal factors and their adolescent children's depressive symptoms using nationally representative data. Also, we examined mother-child interactions and maternal influences by focusing specifically on family dinners in which both the mother and the adolescent participated, rather than simply focusing on the existence or frequency of family dinners, as in other studies [32,33]. We considered not only the child-related factors of adolescent depression, but also the maternal factors, such as the mother's depressive symptoms, education level, household income, marital status, region, work schedule, working hour, current alcohol drinking status, and limitation of activities.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%